Exosomes from EV71‐infected oral epithelial cells can transfer miR‐30a to promote EV71 infection. (5th February 2020) - Wang, Yan; Zhang, Shuting; Song, Weijian; Zhang, Weixin; Li, Jiasu; Li, Chengxi; Qiu, Yingying; Fang, Yuanchun; Jiang, Qian; Li, Xia; Yan, Bin
Abstract: Objective: As an extracellular vesicle, exosomes can release from virus‐infected cells containing various viral or host cellular elements and could stimulate recipient's cellular response. Enterovirus 71 (EV71), a single‐strand positive‐sense RNA virus, is known to cause hand, foot, and mouth disease (HFMD) in children and bring about severe clinical diseases. Methods: Separated the human oral epithelial cells (OE cells) from normal buccal mucosa through enzyme digestion. Performed a comprehensive miRNA profiling in exosomes from EV71‐infected OE cells through deep small RNA‐seq. Using the Human Antiviral Response RT Profiler PCR Array profiles to explore the interactions of innate immune signaling networks with exosomal miR‐30a. Knocked out the MyD88 gene in macrophages using CRISPR/Cas9‐mediated genome editing method. Results: Our study demonstrated that the miR‐30a was preferentially enriched in exosomes that released from EV71‐infected human oral epithelial cells through small RNA‐seq. We found that the transfer of exosomal miR‐30a to macrophages could suppress type Ⅰ interferon response through targeting myeloid differentiation factor 88 (MyD88) and subsequently facilitate the viral replication. Conclusions: Exosomes released from EV71‐infected OE cells selectively packaged high level of miR‐30a that can be functionally transferred to the recipient macrophages resulted in targeting MyD88 and subsequently inhibited type I interferon production in receipt cells, thus promoting the EV71 replication.